Some Improved Ratio, Product, and Regression Estimators of Finite Population Mean When Using Minimum and Maximum Values. (17th November 2013) - Khan, Manzoor; Shabbir, Javid
Abstract : Efficient estimation of finite population mean is carried out by using the auxiliary information meaningfully. In this paper we have suggested some modified ratio, product, and regression type estimators when using minimum and maximum values. Expressions for biases and mean squared errors of the suggested estimators have been derived up to the first order of approximation. The performances of the suggested estimators, relative to their usual counterparts, have been studied, and improved performance has been established. The improvement in efficiency by making use of maximum and minimum values has been verified numerically.